Activation of p300 Histone Acetyltransferase Activity Is an Early Endothelial Response to Laminar Shear Stress and Is Essential for Stimulation of Endothelial Nitric-oxide Synthase mRNA Transcription - Chen, Wei (American Society for Biochemistry and Molecular Biology, 2008)
Previous studies have shown that the acute stimulation of endothelial nitric-oxide synthase (eNOS) mRNA transcription by laminar shear stress is dependent on nuclear factor κ B (NFκB) subunits p50 and p65 binding to a shear stress response element (SSRE) in the human eNOS promoter and that mutation of the SSRE abrogates the shear-stimulated increase in eNOS promoter activity. In the present study, we found that although shear markedly increased eNOS mRNA, the increase in nuclear translocation of p50 and p65 caused by shear was only 2-fold, suggesting that shear has additional effects on NFκB cofactor activity beyond nuclear translocation. Chromatin immunoprecipitation assays showed that virtually no p50 or p65 was bound to the eNOS promoter at base line but that shear increased the binding of these subunits to the human eNOS SSRE by 10- to 20-fold. Co-immunoprecipitation studies demonstrated during the first 30 min of shear p300 bound to p65. Shear also increased p300 histone acetyltransferase (HAT) activity by 2.5-fold and increased acetylation of p65. The increase in eNOS mRNA caused by shear was completely blocked by pharmacological inhibition of p300/HAT activity with curcumin or by p300 small interfering RNA. Chromatin immunoprecipitation assays also showed that shear stimulated acetylation of histones 3 and 4 at the region of the eNOS promoter SSRE and extended 3′ toward the eNOS coding region. This was associated with opening of chromatin at the SSRE. In conclusion, these studies reveal a previously unknown role of p300/HAT activation as a very early response to shear that is essential for increasing eNOS mRNA levels.